Economic openness, exchange rate volatility, and the role of financial development - Habibi, Masoumeh (2015)
This study employs a panel of 59 countries over the period 1980-2011, applying the Two-Step System GMM, to study the relationship between the trade-weighted real exchange rate volatility and openness of an economy, taking the role of financial development level into account. In order to capture the role of financial development level, interaction terms are introduced into the regression and thresholds of financial development are calculated above which, higher financial and trade openness have a stronger impact on real exchange rate volatility. The findings suggest that; (a) higher levels of trade openness as well as financial openness are associated with lower exchange rate volatility, (b) countries with higher levels of financial development experience a stronger negative effect of financial openness on real exchange rate volatility, (c) the effect of trade openness on exchange rate volatility is independent from the level of financial development.